2022
DOI: 10.3390/foods11203165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Storage Temperature on the Enzymatic Activity of Apis mellifera Royal Jelly

Abstract: Royal Jelly is a nutrient secretion of nurse bees and a high interest functional food in human nutrition. Very little information is available on its chemical composition integrity and enzymatic activity during shelf life and assessment of new freshness markers are desirable for its conservation. In this study, the activity of glucose oxidase, five proteases and two antioxidant enzymes in refrigerated and frozen Royal Jelly for different storage times was preliminary investigated. Refrigeration determined a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The evaluated samples that showed their highest proteolytic activities at pH 9 were BB/RJ (8.4 ± 0.17 U), RJ (7.28 ± 0.17 U), and the tri-mix (7.11 ± 0.16 U) (Table 5). The presence of proteases in RJ has been previously hypothesized and discussed, but only a trypsin-like protease and two serine-proteinases in RJ derived from thoracic glands were identified [15]. Matsuoka et al (2012) indicated that RJ proteins consumed by honeybee queen larvae are hydrolyzed by enzymes in the larvae that are alkaline in nature, as these activities were stronger in the alkaline range at pH 9, at which most bands were hydrolyzed.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The evaluated samples that showed their highest proteolytic activities at pH 9 were BB/RJ (8.4 ± 0.17 U), RJ (7.28 ± 0.17 U), and the tri-mix (7.11 ± 0.16 U) (Table 5). The presence of proteases in RJ has been previously hypothesized and discussed, but only a trypsin-like protease and two serine-proteinases in RJ derived from thoracic glands were identified [15]. Matsuoka et al (2012) indicated that RJ proteins consumed by honeybee queen larvae are hydrolyzed by enzymes in the larvae that are alkaline in nature, as these activities were stronger in the alkaline range at pH 9, at which most bands were hydrolyzed.…”
Section: Samplementioning
confidence: 99%
“…The antioxidant activities derived from Major Royal Jelly Proteins (MRJPs) and peptides include scavenging activities, cholesterol-lowering effects, and anti-hypertensive ability and support the ongoing applications of available proteases [13,14]. However, it is difficult to know whether these enzymes are produced by the bee and secreted in RJ or whether they are of vegetal origin, which encourages more investigations in this area [15].…”
Section: Introductionmentioning
confidence: 99%
“…Milone et al [351] also observed a reduction in the average RJ per cell between control and pesticide-exposed colonies (283 mg vs. 198 mg, respectively), but the difference was not statistically significant. The complete knowledge of the RJ components is essential for defining the standard composition and assessment of the quality of marketed products containing RJ [349][350][351][352][353]. Some countries, like Switzerland, Bulgaria, Brazil, and Uruguay, have defined national standards for RJ.…”
Section: Usage References Pediatricsmentioning
confidence: 99%
“…Therefore, it is likely that apisin could be used as an indicator for the evaluation of RJ quality. MRJP1, the main constituent of apisin, plays an essential role not only in the assessment of RJ quality, but also in the determination of RJ freshness [349][350][351][352][353]. However, properties of MRJP1 are dependent on storage conditions.…”
Section: Usage References Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation